The americanization of West Virginia : creating a modern industrial state, 1916-1925 - Hennen, John, 1951-
Local teachers and ministers extolling the virtues of hard work and loyalty to God and country. Veterans' groups and women's clubs promoting the military fighting radicalism, and equating business and patriotism. Industrial leaders gaining legal as well as moral influence over national domestic policy. Such scenes might seem to be lifted from a Sinclair Lewis novel or a Contract with America publicity video. But as John C. Hennen shows in this piercing analysis of early-twentieth-century American political culture, from 1916 to 1925 ""Americanization"" became the theme -- indeed, the script